Multiple myeloma presenting as a cervical intraforaminal tumor: A case report and review of literature - Jankovic, Dragan; Kalasauskas, Darius; Keric, Naureen; Ottenhausen, Malte; Ringel, Florian (Frontiers in Surgery, 2023)
Multiple myeloma (MM) is a haematological malignancy with characteristic clonal plasma cell proliferation and production of monoclonal immunoglobulins. Although it can often metastasize to the bony spine, completely extravertebral and extra-/intradural manifestations are exceedingly rare. We show in this case report a 51-year-old male patient with cervical extradural and intraforaminal MM who was surgically treated in our department. Clinical findings and radiological images were retrieved from medical records and imaging system. This unusual localization of MM and similar cases in the literature are reviewed in detail. The patient underwent tumor resection via ventral approach and postoperative MRI demonstrated a sufficient decompression of neural structures. No new neurological deficits at subsequent follow-ups was observed. Although 7 cases of extramedullary extradural manifestation of multiple myema have been described in the literature so far, this is the first case of intraforaminal extramedullary multiple myeloma located in the cervical spine and treated by surgery.